Green economics and strategies for business sustainability - Yıldırım, Seda; Demirtaş, Işıl, 1980-; Malik, Firdous Ahmad, 1988- (IGI Global Scientific Publishing, 2025)
"This book synthesizes cutting-edge research on a wide range of topics- from green marketing and sustainable supply chains to climate change mitigation and eco-tourism- to offer actionable recommendations for policymakers, businesses, and communities"--